Acute effects of movement velocity on blood lactate and growth hormone responses after eccentric bench press exercise in resistance-trained men - Calixto, R. D.; Verlengia, R.; Crisp, A. H.; Carvalho, T. B.; Crepaldi, M. D.; Pereira, A. A.; Yamada, A. K.; da Mota, G. R.; Lopes, C. R. (Biology of Sport, 2014)
This study aimed to compare the effects of different velocities of eccentric muscle actions on acute blood lactate and serum growth hormone (GH) concentrations following free weight bench press exercises performed by resistance-trained men. Sixteen healthy men were divided into two groups: slow eccentric velocity (SEV; n = 8) and fast eccentric velocity (FEV; n = 8). Both groups performed four sets of eight eccentric repetitions at an intensity of 70% of their one repetition maximum eccentric (1RMecc) test, with 2-minute rest intervals between sets. The eccentric velocity was controlled to 3 seconds per range of motion for SEV and 0.5 seconds for the FEV group. There was a significant difference (P < 0.001) in the kinetics of blood lactate removal (at 3, 6, 9, 15, and 20 min) and higher mean values for peak blood lactate (P = 0.001) for the SEV group (9.1 ± 0.5 mM) compared to the FEV group (6.1 ± 0.4 mM). Additionally, serum GH concentrations were significantly higher (P < 0.001) at 15 minutes after bench press exercise in the SEV group (1.7 ± 0.6 ng · mL-1) relative to the FEV group (0.1 ± 0.0 ng · mL-1). In conclusion, the velocity of eccentric muscle action influences acute responses following bench press exercises performed by resistance-trained men using a slow velocity resulting in a greater metabolic stress and hormone response.